On Integral Inequalities of Hermite-Hadamard Type for s-Geometrically Convex Functions - Tian-Yu Zhang; Ai-Ping Ji; Feng Qi (Abstract and Applied Analysis)
The authors introduce the concept of the s-geometrically convex functions. By the well-known Hölder inequality, they establish some integral inequalities of Hermite-Hadamard type related to the s-geometrically convex functions and apply these inequalities to special means.